Laporan Kasus: Hipertensi Disertai Obesitas - Syamsir, Feryansyah Akhbar; Makmum, Armanto (Indonesian Journal of Health, 2024)
Hypertension is a non-communicable disease that can cause death without causing symptoms or is asymptomatic, so this disease is often known as the "Silent Killer". According to Riskesdas 2018, it was found that 34.1% of the population in Indonesia ≥ 18 years old suffered from hypertension, namely around 63.4 million people. In South Sulawesi alone, around 8% of the population suffers from hypertension. Hypertension is a multifactorial disease that occurs in a person. Obesity or excess body weight is a risk factor for hypertension. The patient in this case is a 47 years old woman who has been undergoing treatment for hypertension for 7 years accompanied by obesity. Her complaint on arrival was pain in the pit of the stomach accompanied by a history of hypertension, diabetes mellitus and obesity. The patient was diagnosed with Grade 2 Hypertension on Treatment, Type 2 Diabetes Mellitus, Dyspepsia, and Obesity who was given therapy in the form of Amlodipine 10 mg 1x1, Glimepiride 2 mg 1x1, Metformin 500 mg 1x1, and Antacid 3x1. Providing pharmacological intervention produced good results, namely controlling the patient's blood pressure and blood sugar. The hypertension suffered by the patient is hypertension that is caused by several predisposing factors in the patient, namely obesity, diabetes mellitus, lifestyle, age and gender